Launching the Global Foresight for Food and Agriculture Tool - Wiebe, Keith; Dunston, Shanila; Woodhill, Jim; Prager, Steven; Perez, Ignacio (2019)
Keith Wiebe, Shanila Dunston, Jim Woodhill, Steven Prager, and Ignacio Perez WEBINAR Launching the Global Foresight for Food and Agriculture Tool Co-Organized by the Food Security Portal, IFPRI, and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) DEC 18, 2019 - 10:00 AM TO 11:00 AM EST